2017
DOI: 10.1007/s00572-017-0784-x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza effects on plant performance under osmotic stress

Abstract: At present, drought and soil salinity are among the most severe environmental stresses that affect the growth of plants through marked reduction of water uptake which lowers water potential, leading to osmotic stress. In general, osmotic stress causes a series of morphological, physiological, biochemical, and molecular changes that affect plant performance. Several studies have found that diverse types of soil microorganisms improve plant growth, especially when plants are under stressful conditions. Most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 247 publications
6
70
0
2
Order By: Relevance
“…a,b). Water transport through AM fungal hyphae has been proposed by many studies, but not demonstrated directly (Santander et al ., ). It is hypothesized that transpiration creates osmotic gradients between the root and fungal cells and water moves along the gradients, which could be tested in the future.…”
Section: The Frontiers: Phosphate Translocation and Exportmentioning
confidence: 97%
“…a,b). Water transport through AM fungal hyphae has been proposed by many studies, but not demonstrated directly (Santander et al ., ). It is hypothesized that transpiration creates osmotic gradients between the root and fungal cells and water moves along the gradients, which could be tested in the future.…”
Section: The Frontiers: Phosphate Translocation and Exportmentioning
confidence: 97%
“…Moreover, increases in the quality of the vast majority of crops using arbuscular mycorrhizal (AM) fungi has also been reported, showing improved uptake of water and some nutrients such as K or N, and especially P . Its use must therefore be a main factor in the context of sustainable agriculture aimed at a reduction of inputs into plant production . Nevertheless, there is no information about the effect of AM fungal inoculation on the quality of strawberry fruits in relation to their antioxidant profiles, concentration, and activities.…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, increases in the quality of the vast majority of crops using arbuscular mycorrhizal (AM) fungi has also been reported, showing improved uptake of water and some nutrients such as K or N, 18 and especially P. 19,20 Its use must therefore be a main factor in the context of sustainable agriculture aimed at a reduction of inputs into plant production. 20,21 Nevertheless, there is no information about the effect of AM fungal inoculation on the quality of strawberry fruits in relation to their antioxidant profiles, concentration, and activities. We therefore aimed to study this interaction here in the context of the introduction of a new productive strain to be established in andisols with low P availability and to provide some information about promoting the production of high-quality strawberry fruit supported by sustainable management.…”
Section: Introductionmentioning
confidence: 99%
“…Outros possíveis mecanismos de sobrevivência e resistência das plantas a estresses, que podem estar relacionados à infecção micorrízica, são o aumento na produção de enzimas antioxidantes (Wu & Zou, 2009), alteração dos níveis hormonais e mudanças na condutância estomática, aumento do conteúdo de água dos tecidos vegetais, dos teores de clorofila e das taxas fotossintética (Zhu et al, 2012;Frosi et al, 2016) e transpiratória (Harris-Valle et al, 2009;Zhu et al, 2012;Santander et al, 2017). Em condições de campo, também se deve considerar, nestes mecanismos de interação solo-planta-fungo, a influência do micélio fúngico na mineralização da matéria orgânica do solo (Paterson et al, 2016), na aquisição de nutrientes pelo hospedeiro (Bender et al, 2015;Thirkell et al, 2017), bem como a importância física de seu exudato, a glomalina (Kohler et al, 2017), que pode favorecer a formação de agregados mais estáveis (Dai et al, 2015;Qin et al, 2017) e mais aptos a trocas de água e ar entre solo e raízes (Al-Kaisi et al, 2014).…”
Section: Discussionunclassified